Implementation of Hospital Management Information System for Optimizing Healthcare Service Operations at A Hospital - Rotua Novita Sinaga; Mitra; Kirby Saputra (LPPM Universitas Harapan Bangsa, 2024)
Computer-based Hospital Information Systems (HIS) are increasingly crucial, yet realizing them requires more effort than merely developing the system. Government regulations mandate the implementation of HIS in every hospital. With HIS, data processing becomes easier, yielding rapid, precise, accurate, and up-to-date information tailored to user needs. This study aims to investigate the implementation of HIS to optimize healthcare service operations at the Dr. Sukirman Military Hospital in Pekanbaru. It employs a qualitative descriptive research design with a case study approach using interviews. The study took place at Dr. Sukirman Military Hospital from November to December 2023, focusing on HIS implementation. Data collection techniques included in-depth interviews, participatory observation, and document review supported by a checklist related to HIS implementation. Data were collected through in-depth interviews with six informants, direct involvement in informant activities through observation, and document review with a checklist. Data analysis employed fishbone analysis, and data validity was tested using the triangulation method. Findings revealed that human resources lacked skills, experience, motivation, responsiveness, needed socialization, supervision, and that socialization and supervision methods in HIS implementation were lacking. Moreover, the material, machine, and environment aspects were still ineffective in-service quality and operational aspects. Therefore, there is a need to enhance human resource competencies through training and supervision to improve the quality of HIS implementation, and there is a need to develop systems for HIS implementation to optimize hospital operations.